The Use of Slang Among Pageant Lovers on the Instagram Account @Dpidamu: A Semantic Study - Nurul Karimah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This research is motivated by a phenomenon observed on Instagram, particularly on the pageant lovers community account @dpidamu. The shift from standard Indonesian to slang forms of language has led to various issues, such as obscured meanings, violations of linguistic rules, and the potential for misunderstandings in everyday communication. This study aims to identify and analyze the forms of slang language from a semantic perspective and to examine language habits within a community as an impact of social media use, particularly Instagram. This research employs a qualitative descriptive approach. The primary focus is to observe and analyze the linguistic forms that appear in everyday communication activities on the Instagram account @dpidamu. The findings reveal ten slang expressions categorized into six groups: interjection forms, meaning extension, affective and relational forms, meaning reduction, and meaning association. The use of slang on the @dpidamu Instagram account indicates that slang is not merely a deviation from standard rules but also a manifestation of linguistic creativity and the social identity of young generations in online interactions. From a semantic perspective, this phenomenon demonstrates that meaning change cannot be separated from the social, cultural, and psychological contexts of its speakers. The use of slang serves as a medium for expressing emotions, building group solidarity, and symbolizing lifestyle in the digital world.